OBSESSIVE COMPULSIVE DISORDER - Ramasamy, Revathee; Westa, Wayan; Ratep, Nyoman (Bali Journal of Medical and Health Sciences; vol 1no1 2013)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Obs e ss i ve c ompu l sive disord e r ( O CD) is a n a n x ie t y disor d e r c h ar ac te r i z e d b y in t rusive thou g hts that p r odu c e un ea siness, a pp r e h e nsion, f e a r, or wo r r y , b y r e p e t i t i ve b e h a viors a i m e d a t r e d u c ing t h e a ssoc i a ted a nx ie t y , or b y a c omb i n a t ion of such obsessions a nd c ompu l sion s . OCD suf fe r e rs g e n e r a l l y r e c o g ni z e their ob s e ss i ons a nd c ompu l sions a s ir ra t i on a l, a nd m a y b e c ome fu r t h e r dis t r e ssed b y th i s r e a l i z a t i on. A n Epid e m i olo g ic a l C a tch m e nt A re a ( ECA) stu d y s h ow e d a l i f e t i me p re v a le n c e of OCD of 2.5 % . B io l o g i c a l, ps y c hol o g i c a l a nd p s y c ho s o c ial a ll pl a y a ro l e in ca using t he disord e r. A dia g nosis of OCD is d ra wn f r om i t s c l i nic a l p re s e ntations. The Di a g nostic a nd S tatis t ic a l Man ua l of Ment a l Disord e rs, F our t h Edit i on, T e x t R e vis i on ( D S M - I V- TR) is used to a id the dia g nosis of OCD. Th e r a pies for OCD a r e in the fo r m of p s y c ho t h e r a p y a nd p s y c hoph a rm ac ol o g y . OCD s y m pto m s p e rsist a t mo d e r a te lev e ls e v e n followi n g a d e qu a te tr ea t m e nt c our s e a nd a c omp l e te l y s y mp t o m - f ree p e riod is un c om m on. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}